3D Printed Geometries on Textile Fabric for Garment Production - Spahiu, Tatjana; Piperi, Erald; Ehrmann, Andrea; Shehi, Ermira; Rama, Dudina (Progress in Digital and Physical Manufacturing - Proceedings of ProDPM'19)
Within the fashion industry, 3D printing can be used for producing individualized products by 3D printing on textile fabrics. One of the main issues of 3D printed geometries on textile fabrics is the adhesion between both materials. Continuing our previous research, other textile fabrics are used as substrate for 3D printing. Again, washing tests which simulate the real use of the textile fabric for garment production indicate that round shapes and thin objects are uncritical to be washed compared to higher objects and square shapes, which tend to separate after the first or the second washing cycle. For nine textile materials under investigation, no separation was found at all for the first 5 washing cycles for two of them. Finally, a full construction cycle including 2D and 3D design, simulation, 3D printing and garment production is presented.
Keywords: 3D printing; Textile fabric; Garments production